THE IMPACT OF HEAD OF BED ELEVATION ON OPTIC NERVE SHEATH DIAMETER IN CERVICAL COLLAR APPLIED HEALTHY VOLUNTEERS - SANRI, ERKMAN; KARACABEY, SİNAN (ELSEVIER SCIENCE INC, 2019)
Background: Guidelines recommend placing a cervical collar (c-collar) until spinal injury is excluded. Previous studies have shown that c-collar placement increases intracranial pressure (ICP), which can worsen outcomes for trauma patients who are at risk of increased ICP. Head of bed elevation (HBE) has been found to decrease ICP. However, there is no consensus in the literature for the optimal degree of HBE to decrease ICP. Objective: We aimed to find an optimal HBE degree to decrease ICP to its baseline values in healthy volunteers with increased ICP caused by c-collar. Methods: This is a randomized controlled and blinded study performed in healthy volunteers. Two sonographers measured the optic nerve sheath diameter (ONSD) of each subject's eyes separately for different time points. Then, we calculated a mean ONSD value for five time points: before c-collar placement (T-0), 5 and 20 min in supine position after c-collar placement (T-5 and T-20), and 5 and 20 min after HBE (T-25 and T-40). We randomized the subjects into three groups of HBE: 15, 30, and 45 degrees, and compared the mean ONSD values among groups. Results: All groups were similar with regard to baseline demographics and ONSD measurements before HBE. We found significant increases in mean ONSD values at T-5 and at T-20 caused by the c-collar. Thirty and forty-five degrees of HBE for 20 min decreased ONSD to its baseline values. The inter-rater reliability of the sonographers was > 0.9. Conclusions: Our results show that c-collar increases ONSD in healthy volunteers. Elevating the head of the bed 30 and 45 degrees for 20 min decreased ONSD to baseline values. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: backrest elevation; cervical collar; head of bed elevation; intracranial pressure; optic nerve sheath diameter; ultrasound; INTRACRANIAL-PRESSURE; MANAGEMENT